TASK-BASED LANGUAGE TEACHING IN TEACHING SPEAKING SKILL AT ONE VOCATIONAL HIGH SCHOOL IN CIMAHI - Supriatna, Asep Koswara (2016)
Speaking is an important aspect in language learning assisting people to convey ideas and maintain social relationship with others. However, some students are still unable to speak English fluently although they have learned it for many years. Thus, this study aims to investigate whether Task-Based Language Teaching (TBLT) is effective to improve the students' speaking ability. This study also aims to find out the students' responses to the implementation of TBLT. This study involved one class and total number of students was 36 students by employing a quasi-experimental design at one vocational high school in Cimahi. The study was conducted by using multiple pre-test and post-test. Therefore, the findings of the study were based on pre-test, treatments, and post-test. The results of this study reveal that Task-Based Language Teaching (TBLT) was effective to improve the students' speaking ability. The effectiveness was seen from the progress of the students' scores between the pre-test and the post-test. In pre-test, the mean score of fluency was 61.1 and 62.81 for accuracy. In post-test, the mean score of fluency was 71.45 and 74.69 for accuracy. Then t-test for fluency was 7.05. and t-test for accuracy was 8.31. with t critical or table was 2.081. It meant that H1 was accepted. It indicated that there was significant improvement of students' speaking in terms of fluency and accuracy. The findings above suggest that TBLT can be applied in teaching speaking skill even though students still need further treatments in order to develop their speaking. --- Berbicara merupakan aspek penting dalam pembelajaran bahasa membantu orang untuk menyampaikan ide dan menjaga hubungan sosial dengan orang lain. Namun, beberapa siswa masih tidak dapat berbahasa Inggris dengan lancar meskipun mereka telah belajar selama bertahun-tahun. Dengan demikian, penelitian ini bertujuan untuk menyelidiki apakah Pengajaran Bahasa Task-Based (TBLT) efektif untuk meningkatkan kemampuan berbicara siswa. Penelitian ini juga bertujuan untuk mengetahui tanggapan siswa terhadap pelaksanaan TBLT. Penelitian ini melibatkan satu kelas dan jumlah siswa adalah 36 siswa dengan menggunakan desain kuasi-eksperimental di salah satu SMK di Cimahi. Penelitian dilakukan dengan menggunakan beberapa pre-test dan post-test. Oleh karena itu, temuan penelitian didasarkan pada pre-test, perawatan, dan post-test. Hasil penelitian ini mengungkapkan bahwa Task-Based Language Teaching (TBLT) adalah efektif untuk meningkatkan kemampuan berbicara siswa. Efektivitas dilihat dari kemajuan skor siswa antara pre-test dan post-test. Dalam pre-test, nilai rata-rata dari kefasihan adalah 61,1 dan 62,81 untuk akurasi. Dalam post-test, nilai rata-rata dari kefasihan adalah 71,45 dan 74,69 untuk akurasi. Kemudian t-test untuk kelancaran adalah 7.05. dan t-test untuk akurasi adalah 8.31. dengan t kritis atau meja adalah 2,081. Ini berarti bahwa H1 diterima. Hal ini menunjukkan bahwa ada peningkatan yang signifikan dari berbicara siswa dalam hal kelancaran dan akurasi. Temuan di atas menunjukkan bahwa siswa masih perlu perawatan lebih lanjut untuk mengembangkan berbicara mereka.